Scoping review protocol to understand the conceptualisation, implementation and practices of health promotion within the context of primary healthcare in Africa - Nkangu, Miriam; Obegu, Pamela; Asahngwa, Constantine; Shiroya, Veronica; Gobina, Ronald; Agbaw-Ebai, Fleur Pembe; Keboa, Mark; Foretia, Denis (BMJ open, 2021)
Introduction The ongoing COVID-19 pandemic has highlighted the importance of health promotion in empowering and sustaining communities, as well as the need to build resilient health systems and work collectively with other sectors to protect and promote health. The WHO has mainstreamed health promotion in the Global health agenda. However, the definition and practices of health promotion in Africa are not well understood and documented, with often, an interchangeable use of the concept of health promotion and health prevention. This scoping review is to explore how health promotion is defined and practised in Africa and identify gaps in its implementation within the framework of the Ottawa Charter. - Methods and analysis The scoping review will employ the approach described by Arksey and O’Malley in 2005. The approach consists of five stages: (1) formulating the research questions, (2) identifying relevant studies, (3) selecting eligible studies, (4) charting the data and (5) collating, summarising and reporting the results. This protocol employed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P). The review will apply the PRISMA extension for scoping reviews to present the results. The scoping review will adapt the five principles set forth in the Ottawa Charter to categorise the outcomes and uses its strategies to define the interventions. Data bases searched are Ovid Medline, Embase, Cochrane Library, CINAHL, SCOPUS, CABI, JBI Evidence Synthesis and grey literature. The database last searched was January 2021. - Ethics and dissemination This review does not require ethics approval. Our dissemination strategy includes peer review publication, policy brief, presentation at conferences and relevant stakeholders.
Gesehen am 04.10.2022